Polyubiquitination of lysine‐48 is an essential but indirect signal for MHC class I antigen processing. Issue 3 (15th January 2015) - Fiebiger, Benjamin M.; Pfister, Heike; Behrends, Uta; Mautner, Josef
<x xml:space="preserve">Abstract</x> Peptides presented on major histocompatibility complex (MHC) class I molecules are generated via cytosolic proteolysis. However, the nature of the endogenous peptide precursors and the intracellular processing steps preceding protein degradation remain poorly defined. Here, we assessed whether ubiquitination is an essential signal for proteasomal cleavage of antigen substrates in human cells. Conversion into antigenic peptides occurred in the absence of any detectable N‐terminal ubiquitination of the model antigens, and did not require the presence of any of the four types, nor a minimum number of ubiquitinatable amino acids within the antigen substrate. However, the knockdown of ubiquitin, expression of a lysine 48 (K48) ubiquitin mutant, or inhibition of proteasome‐associated deubiquitinases significantly impaired antigen presentation. The results presented here are consistent with a model in which the binding of the antigen substrate by an adaptor protein leads to its K48‐polyubiquitination and the subsequent delivery of the antigen cargo for degradation by the 26S proteasome. Altogether, these findings show an important but indirect role of K48‐polyubiquitination in preproteasomal antigen sampling.